Esophageal Varices Rebleeding Prophylaxis Treatment: Who is the Champion? - Lesmana, Cosmas Rinaldi Adithya (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Portal hypertension (PH) is still a big challenge in clinical practice, where the presence of esophageal varices (EV) is the most common complication found in liver cirrhosis (LC) patients. The progression of PH condition in LC patients would lead to decompensated stage with more complications, such as variceal bleeding, the presence of ascites, hepatic encephalopathy, and hepatorenal syndrome.[1,2] Bleeding of EV (BEV) is a critical clinical which carry high mortality. Therefore, not only early detection and how the PH condition can be diagnosed well, but also how we can manage to prevent its complication, especially for primary as well as secondary BEV prophylaxis.[3]